ACID WASH INFLUENCES ON PHYSICOCHEMICAL CHARACTERISTICS OF BAMBOO LEAVES ASH (Jurnal Teknologi (Sciences & Engineering), 2023)
Silica production from sandstone requires tremendous fossil resources that threaten our environment. Hence, greener resources from biomass should be utilized. One of them is from bamboo leaves which contain rich silica in ash. Even so, acid wash should be applied to achieve higher silica purity. This work aims to investigate the acid wash influences on the physicochemical characteristics of bamboo leaves ash (BLA). The treatment used 1 mol/L HCl under 1-h, 2-h, and no acid wash as a control. The BLA crystallography indicates a fully amorphous phase of silica. Interestingly, 1-h acid wash precisely reduces the silica purity from 95.35% to 94.74%, but it then increases to 96.06% under 2-h acid wash. It is also notified that the longer acid wash duration could alleviate leaves’ mechanical strength. After calcination, consequently, a smaller average particle size of BLA was nominated under 2-h acid wash (6.32 mm). It was then followed by 1-h acid wash (21.32 mm) and no acid wash (149.44 mm). The 2-h acid wash is concluded able to intensify silica purity as well as reduce the particle size of BLA. Finally, acid wash treatment becomes important to facilitate further BLA extraction in order to achieve high purity of silica.